Pengaruh Intrapersonal Constraints, Interpersonal Constraints dan Risk Attitude Terhadap Travel Intention Pada Destinasi Wisata Lembah Harau - Sintia Anisa; Yasri Yasri (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this study is to analyze the extent of the influence of Intrapersonal Constraints, Interpersonal Constraints and Risk Attitude in increasing Travel Intention in Harau Valley Tourist Destinations. The population studies the entire society with an uncertain number. The research sample is West Sumatran tourists who know the Harau Valley Tourism Destinations and will travel as many as 150 people with the purposive sampling method. The survey method was conducted using a structured questionnaire, where respondents were asked to give their responses to experiments in Harau Valley Tourist Destinations. Covariance-based structural equation modeling (CB-SEM) is used to analyze hypothetical relationships in research models. The findings suggest that all direct effects in the proposed model have a significant influence